Adhesion and dynamic impact wear of nanocomposite TiC-based coatings prepared by DCMS and HiPIMS. (January 2020) - Daniel, J.; Souček, P.; Grossman, J.; Zábranský, L.; Bernátová, K.; Buršíková, V.; Fořt, T.; Vašina, P.; Sobota, J.
Abstract: Nanocomposite nc-TiC/a-C:H coatings exhibit a unique combination of mechanical properties such as high hardness, and low friction and wear. These physical and mechanical properties make those coatings attractive for application in industry. However, the properties of the whole coating/substrate system such as adhesion of the coating to substrate and its response on repeated impact loading known such as dynamic impact wear are also important for industrial applications. Thus, this paper is focused on the adhesion and the dynamic impact wear of nc-TiC/a-C:H coatings prepared by the hybrid PVD-PECVD process. Two series of nc-TiC/a-C:H coatings with a different amount of carbon were deposited onto commonly used industrial cemented tungsten carbide substrates using DC magnetron sputtering (DCMS) and the high power impulse magnetron sputtering (HiPIMS) of a titanium target in argon and acetylene mixture atmosphere. Both series of coatings were analysed using a scratch test and dynamic impact tester with an impact load of 600 N. The HiPIMS prepared coatings exhibited lower thickness and lower thicknesses of the Ti adhesive interlayers between the substrates and coatings than the DCMS prepared coatings. Thus, the adhesion and the impact wear of both series were discussed separately. These properties were discussed with respect to the coating microstructure, phase composition and mechanical properties such as the hardness H, the effective elastic modulus E, and the H/E and H 3 /E 2 ratios. The scratch adhesion of coatings depended on the H 3 /E 2 ratio and coating microstructure, hardness and surface roughness. The impact wear of the nc-TiC/a-C:H coatings depended on the H/E ratio and coating microstructure. Highlights: Hard TiC-based coatings with various structure prepared by DCMS and HiPIMS. Adhesion and impact wear changed as total carbon content increased from 25% to 65%. Scratch adhesion changes were discussed with respect to the structure and H 3 /E 2 ratio. Concept of impact resistance was defined and discussed. Impact wear of hard coatings was related to the coating structure and H/E ratio.